PEMANFAATAN KULIT PETAI (PARKIA SPECIOSA HASSK.) DALAM SEDIAAN HAND SANITIZER SPRAY ALAMI: UTILIZATION OF PETAI SKIN (PARKIA SPECIOSA HASSK.) IN NATURAL HAND SANITIZER SPRAY - Agustin Wijayanti (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2022)
Petai peel (Parkia speciosa Hassk.) contains chemical compounds in the form of alkaloids, saponins and flavonoids. Where these chemical compounds play an active role in having antibacterial activity, especially flavonoid compounds. The purpose of this study was to make a hand sanitizer spray formulation from petai peel extract as a natural antiseptic.In this study, we made hand sanitizer spray preparations with three variations of formulations, what distinguishes one from the other is the concentration of the extract used. Formulation 1 uses 5% extract, formulation 2 uses 10% extract and formulation 3 uses 15% extract. The first step is to prepare tools and materials to make a hand sanitizer spray formulation, then weigh the ingredients needed. Dissolve the petai peel extract with 96% alcohol little by little, then add the other ingredients. Then put in a measuring flask and add aquadest up to 100 ml. Then put it in a bottle of hand sanitizer spray. After that, the finished preparation was then evaluated for stability, including: organoleptic test, pH test, dispersion test, spray condition test, viscosity evaluation, irritation test and antibacterial test using Staphylococcus aureus bacteria using disc diffusion method.The results of the antibacterial test showed that the hand sanitizer spray formulation 3 with a concentration of 15% had the highest inhibitory power with the average value of the inhibition zone being 26.22 ± 0.50 with a very strong category.